2016
DOI: 10.1039/c6nr00492j
|View full text |Cite
|
Sign up to set email alerts
|

Single- and few-layer WTe2and their suspended nanostructures: Raman signatures and nanomechanical resonances

Abstract: Single crystal tungsten ditelluride (WTe 2 ) has recently been discovered to exhibit nonsaturating extreme magnetoresistance in bulk; it has also emerged as a new layered material from which atomic layer crystals can be extracted. While atomically thin WTe 2 is attractive for its unique properties, little study has been conducted on single-and few-layer

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 29 publications
(91 reference statements)
6
37
0
Order By: Relevance
“…Thus, the shift of major peaks and the intensity ratio of the A1(11) and A1(22) peaks can be used as convenient measures to rapidly characterize thickness of GaSe layers. A similar effect has been observed in TMDs like WS 2 , WSe 2 , MoSe 2 , WTe 2 , NbSe 2 , PtSe 2 , GaS, etc …”
Section: Resultssupporting
confidence: 76%
“…Thus, the shift of major peaks and the intensity ratio of the A1(11) and A1(22) peaks can be used as convenient measures to rapidly characterize thickness of GaSe layers. A similar effect has been observed in TMDs like WS 2 , WSe 2 , MoSe 2 , WTe 2 , NbSe 2 , PtSe 2 , GaS, etc …”
Section: Resultssupporting
confidence: 76%
“…Figure 1h displays the Raman spectroscopy of WTe 2 of 2 to 8 layers probed by a 532 nm wavelength laser. The bi-layer shows least peaks and lowest signal, with 6 distinct Raman bands observed around 86.7, 108.3, 120.0, 135.6, 164.2 and 215.3 cm -1 , respectively, in agreement of those reported in previous works [16][17][18]. All spectra are fitted via single Lorentzian and renormalized for visual clarity as seen in Fig.…”
supporting
confidence: 82%
“…Figure b shows the optical microscopy images of 1L, 2L, and 3L WTe 2 and Figure c shows the Raman spectra of corresponding regions in (b) in vacuum conditions. In our previous study, we have observed total 12 peaks in few‐layer WTe 2 . As number of layers decreases to 3L, many peaks' intensities decrease significantly and only four peaks remain robust due to space group evolution from bulk ( C 2v ) to 1L ( C 2h ) WTe 2 .…”
mentioning
confidence: 83%
“…In our previous study, we have observed total 12 peaks in few-layer WTe 2 . [7] As number of layers decreases to 3L, many peaks' intensities decrease significantly and only four peaks remain robust due to space group evolution from bulk (C 2v ) to 1L (C 2h ) WTe 2 . [6] We refer these four peaks as P1, P2, P3, and P4 hereafter (see Figure 1c).…”
mentioning
confidence: 99%